From Website to Moodle in a Blended Learning Context - Buus, Lillian (International Journal of Web-Based Learning and Teaching Technologies, 2016)
This paper presents findings collected from a collaborative implementation project established in Spring 2008 between Aalborg University's IT-department in the Faculty of Social Science (FSS) and the E-Learning Cooperation Unit (ELSA) with the view to implement Moodle in FSS. The purpose of this cooperation was conceived from an organisational desire to establish a virtual learning environment (VLE), where it was possible, to build activities and underpin the pedagogical approach. Another perspective was to further improve the communication between the administration, teachers and students. This paper will highlight the development process and some of the didactic considerations undertaken for the implementation. The evaluations undertaken during the process will also be presented, along with the results collected in the use of Moodle to highlight the educational changes.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9pandsdHQuMjAxNjAxMDEwNA